Iterative Source and Relay Precoder Design for Non-Regenerative MIMO Cognitive Relay Systems - Budhathoki, Krishna Ram; Maleki, Mehdi; Bahrami, Hamid Reza (IEEE transactions on communications, 2015)
The problem of joint precoder design for the source and relay nodes of a cooperative cognitive radio (CR) system is investigated. We consider a non-regenerative relaying secondary CR system with underlay spectrum sharing methodology with the primary users. Based on an expression for the achievable throughput of secondary system, we develop an optimization problem to maximize the throughput subject to power constraints at the secondary source and relay, and an interference power constraint at the primary due to secondary source and relay transmission. First, we derive the structure of each of the relay and source precoding matrices separately assuming the other is known. Then, we propose an iterative technique to jointly design the source and relay precoding matrices. The results are also extended to the case where the direct source-destination link is available. Through simulation, we demonstrate the effectiveness of our proposed approach in improving the achievable throughput, and compare its performance with that of numerical optimization, source only precoding, relay only precoding, and a naive amplify-and-forward method.